1976
DOI: 10.1136/bmj.1.6014.870
|View full text |Cite
|
Sign up to set email alerts
|

Fetal complications of obstetric cholestasis.

Abstract: sodium cromoglycate. This effect was not due to a difference between the patients, since when we recalculated the results using the same 11 subjects for both placebo and sodium cromoglycate they were the same. Sodium cromoglycate has a slight phosphodiesterase inhibiting effect, which might explain the differences' 0; however, it has no effect on the histamine response of human bronchial smooth muscle.' We have also shown that sodium cromoglycate has no effect on tracheal smooth-muscle contraction induced by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
2
4

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(85 citation statements)
references
References 6 publications
1
78
2
4
Order By: Relevance
“…37,38 Although maternal complications from ICP are rare, there are several adverse fetal effects including preterm labor, meconium aspiration, and fetal death. [37][38][39][40] Rencoret and Aste 37 reviewed 32 cases of jaundice in pregnancy (31 out of 32 cases with intrahepatic cholestasis) and reported two fetal deaths and a preterm labor rate of 33.3%. Reid and colleagues 38 analyzed complications in 56 pregnancies with ICP and reported an astonishingly high rate of adverse outcomes (ie, perinatal mortality rate 11%, meconium staining 27%, abnormal antepartum fetal heart rate pattern 14%, and preterm delivery rate 36%).…”
Section: Impact On the Fetusmentioning
confidence: 99%
“…37,38 Although maternal complications from ICP are rare, there are several adverse fetal effects including preterm labor, meconium aspiration, and fetal death. [37][38][39][40] Rencoret and Aste 37 reviewed 32 cases of jaundice in pregnancy (31 out of 32 cases with intrahepatic cholestasis) and reported two fetal deaths and a preterm labor rate of 33.3%. Reid and colleagues 38 analyzed complications in 56 pregnancies with ICP and reported an astonishingly high rate of adverse outcomes (ie, perinatal mortality rate 11%, meconium staining 27%, abnormal antepartum fetal heart rate pattern 14%, and preterm delivery rate 36%).…”
Section: Impact On the Fetusmentioning
confidence: 99%
“…It has been observed that increasing the concentration of bile acids alters the sinoatrial node and induces bradycardia [8]. This mechanism might explain acute fetal death because an association with a chronic cause, such as placental insufficiency, has not been demonstrated [9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…A contrario, les anomalies rythmologiques ne sont pas si fréquentes (16 % seulement des foetus dans la série de cholestase de Reid et al [17]) ; par ailleurs, plusieurs cas de MFIU ont été rapportés en l'absence de signe de gravité (RCF non pathologiques, scores biophysique de Manning et biométries échographiques normaux, concentration des acides biliaires inférieure à 40 M), ce qui pose plusieurs questions :…”
Section: Discussionunclassified